Design And Implementation Of An Embedded Temperature Control System For Laboratory-Scale Pyrolysis Applications - Ahmad Robittah; Ahmad Faqih Habibi; Hafiz Al Farizi; Muhammad Akbar Hariyono; Achmadi; Aulia Rahman (⁠International Journal of Sustainable Social Culture, Science Technology, Management, and Law Humanities, 2026)
Accurate and stable temperature control is essential in laboratory-scale thermal processing, as it directly influences process stability, operational safety, and experimental reproducibility. However, many laboratory thermal systems still rely on manual regulation or simple heating mechanisms without adequate feedback control, resulting in temperature fluctuations and inconsistent performance. This study presents the design and implementation of an embedded temperature control system for laboratory-scale thermal processing, using pyrolysis as an application case study. The proposed system is based on a closed-loop control architecture that integrates a K-type thermocouple, a microcontroller-based control unit, and an electrical heating actuator. A hysteresis-based on–off control strategy is implemented to regulate the heating process and maintain the desired temperature setpoints. The system performance is experimentally evaluated at operating temperatures of 300 °C, 400 °C, and 500 °C under different processing durations. Experimental results demonstrate that the developed system provides stable and reliable temperature regulation across all tested conditions. The system exhibits a rapid heating response, minimal overshoot, and acceptable steady-state temperature deviations, even at elevated operating temperatures. Long-duration operation confirms the robustness and reliability of the control strategy. These results indicate that the proposed embedded temperature control system offers a practical and cost-effective solution for laboratory-scale thermal processing applications requiring stable and repeatable temperature control.